PSYCHOLOGICAL ANALYSIS OF NICOLE BARBER IN DEALING WITH CONFLICT IN MARRIAGE STORY MOVIE - Swecandari Wake, Yosephina Feolita (LITERA : Jurnal Bahasa Dan Sastra, 2021)
ABSTRACTIn a movie, there are intrinsic elements and extrinsic elements. One of the elements thatmakes a film interesting is the conflict and the characters. Conflicts that occur can be inthe form of physical or psychological conflicts. A person's psychology can affect theemergence of a conflict in a character and can also affect how a character can solve theirproblem. The undergraduate thesis entitled "Psychological Analysis of Nicole Barber inDealing with Conflict in Marriage Story Movie" aims to show that there is a relationshipbetween a divorce conflict that happened in Nicole Barber and its psychology. MarriageStory was chosen because at present, divorce is a common thing.Keywords: Psychology, Conflict, Characters, Marriage StoryABSTRAKDalam sebuah film, terdapat unsur intrinsik dan unsur ekstrinsik. Salah satu unsur yangmembuat sebuah film menjadi menarik adalah konflik dan karakternya. Konflik yangterjadi dapat berupa konflik fisik maupun psikologi. Psikologi seseorang dapatberpengaruh terhadap munculnya sebuah konflik dalam sebuah karakter dan juga dapatberpengaruh terhadap bagaimana seorang karakter dapat menyelesaikan masalahnya.Skripsi yang berjudul â€œPsychological Analysis of Nicole Barber in Dealing with Conflictin Marriage Story Movieâ€ bertujuan untuk menunjukkan bahwa terdapat hubunganantara sebuah konflik perceraian yang terjadi pada Nicole Barber dengan psikologinya.Marriage Story dipilih karena pada masa sekarang, perceraian menjadi hal yang seringdijumpai.Kata Kunci: Psikologi, Konflik, Karakter, Marriage Story